Multimodal structure of baroclinic tides in the South China Sea - V. Vlasenko; N. Stashchuk; C. Guo; X. Chen (Nonlinear Processes in Geophysics, 2010)
The modelling of baroclinic tides generated in the northern South China Sea is studied using a fully-nonlinear non-hydrostatic numerical model. The focus of the modelling efforts was on the vertical structure of internal waves in the vicinity of the Luzon Strait. The barotropic tidal flow interacting with a two-ridge bottom topography in the area of the Luzon Strait produces a complex baroclinic tidal signal. A multimodal baroclinic bore with counter-phase displacement of isopycnals generated over the ridges and propagating westward disintegrates into a series of large-amplitude solitary internal waves. The leading first-mode solitary wave of depression is followed by a second mode solitary wave coupled with a packet of short-scale internal waves riding it. Scrutiny of the characteristics of the both wave forms, i.e. the carrier second-mode solitary wave and the packet of short waves, revealed that the short-scale waves are basically concentrated in the upper 500 m layer and attenuate exponentially below it. The short waves exist only thanks to a specific structure of horizontal velocity produced by the second-mode solitary wave. Having equal phase speeds and propagating together for a long distance, this coupled system produces quite a remarkable signal at the free surface, which can be detected by means of remote sensing technique. It was found in a series of sensitivity experiments that the eastern ridge is responsible for the generation of progressive first-mode tidal waves disintegrated into packets of first-mode ISWs. The western ridge produces quite a strong higher-mode signal. The waves generated over the eastern and western ridges interfere in the near-field, and their nonlinear superposition enhances the multimodal signal in the whole domain.